Case report: Rare latent postoperative pseudoaneurysm of internal maxillary artery after Le Fort osteotomy - Victoria Chen; Supritha Nilam; Alexander McMahon; Brennan Leininger; Nora Kahenasa (Oral and Maxillofacial Surgery Cases, 2024)
Background: The Le Fort I osteotomy is a commonly employed and predictable surgical technique used to treat maxillofacial deformities. While considered technically safe, orthognathic surgery can cause significant vascular complications. Presentation: This case report describes a 20-year old male who had undergone a routine Le Fort I osteotomy to treat maxillo-mandibular discrepancy, and subsequently developed an internal maxillary artery pseudoaneurysm that caused uncontrolled hemorrhage and hemodynamic instability. The patient ultimately required interventional radiology coil embolization for source control. Discussion: Although rare, internal maxillary artery pseudoaneurysms continue to be reported as postoperative complications in Le Fort I osteotomies, wherein coil-embolization technique remains a viable option for treatment. Additionally, the presentation of temporal swelling and retrobulbar pain may be useful in diagnosing the existence of a maxillary artery pseudoaneurysm. Conclusion: Pseudoaneurysm of the internal maxillary artery is a possible sequela of orthognathic surgery, and proper monitoring and management can avoid morbid outcomes.